Characterization of joint disease in mucopolysaccharidosis type I mice. Issue 5 (21st June 2013) - de Oliveira, Patricia G.; Baldo, Guilherme; Mayer, Fabiana Q.; Martinelli, Barbara; Meurer, Luise; Giugliani, Roberto; Matte, Ursula; Xavier, Ricardo M.
Summary: Mucopolysaccharidoses (MPS) are lysosomal storage disorders characterized by mutations in enzymes that degrade glycosaminoglycans (GAGs). Joint disease is present in most forms of MPS, including MPS I. This work aimed to describe the joint disease progression in the murine model of MPS I. Normal (wild‐type) and MPS I mice were sacrificed at different time points (from 2 to 12 months). The knee joints were collected, and haematoxylin–eosin staining was used to evaluate the articular architecture. Safranin‐O and Sirius Red staining was used to analyse the proteoglycan and collagen content. Additionally, we analysed the expression of the matrix‐degrading metalloproteinases (MMPs), MMP‐2 and MMP‐9, using immunohistochemistry. We observed progressive joint alterations from 6 months, including the presence of synovial inflammatory infiltrate, the destruction and thickening of the cartilage extracellular matrix, as well as proteoglycan and collagen depletion. Furthermore, we observed an increase in the expression of MMP‐2 and MMP‐9, which could conceivably explain the degenerative changes. Our results suggest that the joint disease in MPS I mice may be caused by a degenerative process due to increase in proteases expression, leading to loss of collagen and proteoglycans. These results may guide the development of ancillary therapies for joint disease in MPS I.